2012
DOI: 10.4236/ss.2012.310096
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Reconsideration of the Lateral Collateral Ligament in the Human Knee: Anatomical Observation and Literature Review

Abstract: In the published literature as well as in the most commonly used textbooks, the lateral collateral ligament (LCL) is described as having 1 attachment at the lateral epicondyle of the femur and another at the head of the fibula. In this article, we reconsider the attachments, the length of the LCL, and the tissues surrounding the LCL by presenting our anatomical observations and by reviewing the literature. Our results have shown that the LCL is not only attached to the lower part of the lateral epicondyle of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Several anatomical studies of the femoral insertion of the PLC have been described, and most authors have indicated large positional variations in the femoral insertion of the LCL and PT. Thus, their accurate positions are still controversial [1, 12–15, 23, 26, 30, 31]. To perform anatomical reconstruction of the PLC using double femoral tunnel techniques, it is necessary to define the femoral insertion of the LCL and PT, and assess their related osseous landmarks.…”
Section: Introductionmentioning
confidence: 99%
“…Several anatomical studies of the femoral insertion of the PLC have been described, and most authors have indicated large positional variations in the femoral insertion of the LCL and PT. Thus, their accurate positions are still controversial [1, 12–15, 23, 26, 30, 31]. To perform anatomical reconstruction of the PLC using double femoral tunnel techniques, it is necessary to define the femoral insertion of the LCL and PT, and assess their related osseous landmarks.…”
Section: Introductionmentioning
confidence: 99%